2022
DOI: 10.3145/epi.2022.nov.03
|View full text |Cite
|
Sign up to set email alerts
|

Use and adoption of digital educommunication media by university professors during the Covid-19 pandemic: cases of the National Autonomous University of Mexico and the Autonomous University of Chihuahua

Abstract: This article analyzes the educational use of digital educommunication media (DEM) by four groups of professors working at the faculties of Philosophy and Letters and of Engineering at the Autonomous University of Chihuahua (UACH) and at the National Autonomous University of Mexico (UNAM). Seven hypotheses and three research questions were posed, which were related to the use of DEM (specifically: images, animations, and video; presentations (PowerPoint/Prezi); digital texts; the Cloud; social media/instant mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous familiarity with online resources was critical in effectively integrating digital tools. Rey-Ronquillo and Machin-Mastromatteo [59] found that 75% of professors from two Mexican institutions had prior experience with virtual education. Throughout the pandemic, most professors in the study (80%) used DEM, such as email, images, animations, video, and cloud-based files.…”
Section: Perception Of Teachers and Academic Staffmentioning
confidence: 99%
“…Previous familiarity with online resources was critical in effectively integrating digital tools. Rey-Ronquillo and Machin-Mastromatteo [59] found that 75% of professors from two Mexican institutions had prior experience with virtual education. Throughout the pandemic, most professors in the study (80%) used DEM, such as email, images, animations, video, and cloud-based files.…”
Section: Perception Of Teachers and Academic Staffmentioning
confidence: 99%